Islamic Banking Development and Its Influence on Unemployment in Indonesia - Fajri, Mohammad Zen Nasrudin (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: This paper aims to discover how the Islamic Bank’s development affects unemployment in Indonesia. It also tries to reveal to what extent the Islamic Bank’s development affects unemployment in Indonesia.Design/Method/Approach: This study is a quantitative research that uses the Generalized Method of Moments (GMM) in analyzing the provincial data spanning from 2010 to 2021in Indonesia.Findings: The findings of this research show that Islamic Bank’s asset has a positive relationship with unemployment in Indonesia, whereby a 1 percent increase in Islamic Bank’s asset will increase unemployment by 0.21%. Likewise, a 1 percent increase in the Third-party Fund of Islamic Bank in Indonesia contributed to a rise in unemployment by 0.09 %. On the contrary, total financing channeled by the Islamic Bank in Indonesia reduced unemployment by 0.13 %. It can be seen from the result that the impact of Islamic Bank development in Indonesia can be seen from the total funds channeled to the business. The more the funds are channeled to the business, the more it can reduce unemployment in Indonesia.Originality/Values: This study is the first to analyze how Islamic Bank would influence unemployment using third-party funds, total assets and total financing.